Calcium oscillations in HEK293 cells lacking SOCE suggest the existence of a balanced regulation of IP3 production and degradation - Octors, Clara; Yoast, Ryan E.; Emrich, Scott M.; Trebak, Mohamed; Sneyd, James (Frontiers in Systems Biology, 2024)
The concentration of free cytosolic is a critical second messenger in almost every cell type, with the signal often being carried by the period of oscillations, or spikes, in the cytosolic concentration. We have previously studied how influx across the plasma membrane affects the period and shape of oscillations in HEK293 cells (Emrich et al, 2021, Cell Rep., 43, 9, 108760: doi 10.1016/j.celrep.2021.108760). However, our theoretical work was unable to explain how the shape of oscillations could change qualitatively, from thin spikes to broad oscillations, during the course of a single time series. Such qualitative changes in oscillation shape are a common feature of HEK293 cells in which STIM1 and 2 have been knocked out. Here, we present an extended version of our earlier model that suggests that such time-dependent qualitative changes in oscillation shape might be the result of balanced positive and negative feedback from to the production and degradation of inositol trisphosphate.